Respiratory Health Status of Rural Women Exposed to Liquefied Petroleum Gas and Solid Biomass Fuel Emissions. Issue 12 (September 2019) - Kaur-Sidhu, Maninder; Ravindra, Khaiwal; Mor, Suman; John, Siby; Aggarwal, Ashutosh N
Combustion of solid biomass fuel (SBF) releases a high concentration of airborne pollutants, resulting in household air pollution (HAP). HAP is considered as a leading risk factor for the development of various respiratory diseases. The increased exposure to HAP significantly affects the health of the vulnerable population, including the women, elderly, and children who stay indoors for most of the time. Considering this, self-reported respiratory health symptoms were assessed using a standard American Thoracic Society (ATS) questionnaire, whereas lung function capacity of women using SBF, liquefied petroleum gas (LPG) and mix fuels were assessed using a cross-sectional study design. Lung function capacity was examined with help of spirometry. Results suggest that compared with LPG users, SBF and mix fuel users had a relatively high prevalence of phlegm (25.7%), cough (54%), and eye irritation (74.3%). Use of SBF was found to be associated significantly with lower forced expiratory volume in the first second of expiration (FEV1 ) values ( P < .01). The study concludes that women cooking with SBF and mix fuels have an impact on lung function and increased prevalence of respiratory symptoms. The findings suggest that women who cook using LPG have improved lung function and respiratory health status. Hence, it is suggested to increase the scope of clean fuel programmes such as Pradhan Mantri Ujjwala Yojana (PMUY) by identifying the barriers for the choice of clean fuel uses for household energy.